The concept of love for knowledge and excellent muslims in transforming human capital: an analysis on gender differences - Nur Hidayah Mohd Abd Malik,; Syaidatun Nazirah Abu Zahrin,; Rezki Perdani Sawai,; Fariza Md. Sham, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The study investigated the gender differences among Muslims’ university students in the aspect of Love for Knowledge, the characteristics of Excellent Muslims and Transformation of Human Capital based on a sample of 600 university students surveyed in Malaysia. The sample was selected using a purposive sampling technique. Data for the study were collected by using structured questionnaire. Inferential statistics of t-test was used to analyze data on gender differences. The findings revealed that there were no gender differences exist between male and female on the features of Love for Knowledge, Characteristics of Excellent Muslims and Transformation of Human Capital. The paper discussed implications of these results on the importance of acquisition of knowledge in order to develop excellent young Muslims and transforming the human capital.